2015
DOI: 10.1039/c5ra02249e
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Thermomyces lanuginosus lipase on ZnO nanoparticles: mimicking the interfacial environment

Abstract: In this study, we propose that enzyme activity on immobilization can be controlled and enhanced by providing the environment mimicking the lipid/water interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 53 publications
3
8
0
Order By: Relevance
“…Zinc oxide, as a versatile nanomaterial, has been proved suitable for biotechnological applications by plenty of studies. There are also several works dealing with enzyme immobilization on ZnO nanoparticles, , while these structures are on the list of the U.S. Food and Drug Administration (21CFRI82.8991) as safe (GRAS). β-Glucosidases (E.C 3.2.1.21) are well-characterized biological catalysts .…”
Section: Introductionmentioning
confidence: 99%
“…Zinc oxide, as a versatile nanomaterial, has been proved suitable for biotechnological applications by plenty of studies. There are also several works dealing with enzyme immobilization on ZnO nanoparticles, , while these structures are on the list of the U.S. Food and Drug Administration (21CFRI82.8991) as safe (GRAS). β-Glucosidases (E.C 3.2.1.21) are well-characterized biological catalysts .…”
Section: Introductionmentioning
confidence: 99%
“…Zinc oxide (ZnO) nanoparticles have been exploited in many fields such as catalysis, drug delivery and biology, where they have unique ability to promote faster electron transfer between the active site of enzymes and substrates, as a potential material in enzyme engineering, however, very little information about their application in immobilization of lipase can be found [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Improved activity of immobilized lipase at elevated temperatures is considered as a major advantage for large scale applications, indicating better temperature adaptability. Studies have reported a similar pattern regarding the immobilization of TLL on different nanomaterials, such as magnetic [ 54 ] and ZnO-coated nanoparticles [ 55 ].…”
Section: Resultsmentioning
confidence: 84%